Developing a Course Materials Sprachbeherrschung Based on Outcome Based Education - Hutagalung, Surya Masniari; Huszka, Balazs; Sari, Tanti Kurnia; Pujiastuti, Suci Pujiastuti (Journal of Languages and Language Teaching, 2024)
Sprachbeherrschung is a study subject in the German Language education department in the faculty of language and art, Universitas Negeri Medan, which teaches four language skills completed by cross culture and social behavior. Therefore, the present study aims to develop teaching material for the subject of Sparachbeherrschung based on outcome. This development research is a qualitative descriptive study. The teaching material was develop based on semester teaching plan arranged in accordance with outcome-based learning principle. The development model used was Thiagarajan model consisted of four steps, i.e. defining, designing, developing, and disseminating. The presented report only consisted three out of four steps, in which disseminating was excluded. Defining step is the step of formulating the idea through need analysis. The designing step is the step of mapping the graduate learning outcome to the subject learning outcome which is associated to the result of need analysis. The developing step was carried out through the activity of material development and expert validation. The experts were three individuals with expertise in material development. the instrument used was validated.Â  Instrument used was in form of questionnaire refers to likert scale. The result of expert validation indicate that the teaching material was suitable for use, with an average score of 90,0.Â